2014
DOI: 10.1039/c3cs60385g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazone-based switches, metallo-assemblies and sensors

Abstract: The hydrazone functional group has been extensively studied and used in the context of supramolecular chemistry. Its pervasiveness and versatility can be attributed to its ease of synthesis, modularity, and most importantly unique structural properties, which enable its integration in different applications. This review provides an overview of the utilization of hydrazones in three supramolecular chemistry related areas: molecular switches, metallo-assemblies and sensors. These topics were chosen because they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
320
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(327 citation statements)
references
References 127 publications
1
320
1
5
Order By: Relevance
“…Hidrazon fonksiyonel grup içeren bileşiklerin endüstride çok çeşitli alanlarda kullanıldığından bahsetmiştik [13]. Elde ettiğimiz hidrazon grubu içeren oligomerler bu anlamda önem taşımaktadır.…”
Section: Bulgular Ve Tartişmaunclassified
See 1 more Smart Citation
“…Hidrazon fonksiyonel grup içeren bileşiklerin endüstride çok çeşitli alanlarda kullanıldığından bahsetmiştik [13]. Elde ettiğimiz hidrazon grubu içeren oligomerler bu anlamda önem taşımaktadır.…”
Section: Bulgular Ve Tartişmaunclassified
“…Hidrazon fonksiyonel grup içeren bileşikleri, organik sentezler, biyomedikal uygulamalar, supramoleküler kimya, metal kovalent bağlı organik yapılar, ilaç salınım sistemleri uygulamaları, dinamik kombinasyon kimyası, boya ve boşluk transfer malzemeleri gibi çeşitli alanlarda bolca kullanmışlardır [13]. Hidrazon grubuı içeren polimerleri ilaç salınım sistemlerinde yaygın bir şekilde kullanmışlardır.…”
Section: Introductionunclassified
“…Deionized double-distilled water was used throughout and test solutions were buffered in a 0.02 mol L -1 solution of acetic acid/ sodium acetate and pH adjusted with dropwise addition of 1 mol L -1 solution of HCl or NaOH. The Schiff's base L, with the chemical name of 1-acenaphthoquinone 1-thiosemicarbazone, was synthesized and purified using a previously reported method [27,28].…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…In the present study, a hydrazone derivative ligand 1-acenaphthoquinone 1-thiosemicarbazone, L (Figure 1) [27,28], is covalently immobilized on a triacetyl cellulose membrane to be used as an effective ionophore with N and O donor atoms for construction of a selective optical sensor for the spectrophotometric determination of Ni 2+ in aqueous solutions. The studied compound as an ionophore is the family of hydrazone which is a kind of asymmetric Schiff's base.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the synthesis of and characterization of newer lanthanide complexes is a potential field of research in inorganic chemistry. Though Sacconi has reported [12] lanthanide complexes of acetylacetone isonicotinoyl hydrazone in the year 1954, a literature review [13][14][15] indicated that the study of such complexes is relatively less when compared with transition metal complexes with this class of ligands.…”
Section: Introductionmentioning
confidence: 99%